THE INFLUENCE OF BOARD OF DIRECTORS' CHARACTERISTICS AND OWNERSHIP STRUCTURE ON SUSTAINABLE DEVELOPMENT - Imam Andika Saputra; Acep Komara; Ahmad Syifaudin (GoAcademica Research dan Publishing, 2026)
This study looked at how ownership structure and board of director traits affected sustainable development in non-banking enterprises listed on the Indonesia Stock Exchange between 2023 and 2025. The Upper Echelons Theory, which highlighted how top management characteristics influenced strategic choices, served as the foundation for the study. Using panel data from annual reports, sustainability reports, and ESG databases, a quantitative method was used. Purposive sampling was used to choose 94 companies for the sample, and multiple linear regression was used to analyze the data. The findings showed that gender diversity and board size had a favorable and substantial impact on sustainable development. Age, education, professional experience, and board independence, on the other hand, had no discernible impact. In terms of ownership structure, foreign ownership had a large negative impact, management and public ownership were not significant, and institutional ownership and ownership concentration showed a positive and significant influence. All independent variables had a significant impact on sustainable development at the same time. The results indicated that improving corporate sustainability performance was mostly dependent on an inclusive board composition and robust institutional oversight.